Effect of tick saliva on immune interactions between Borrelia afzelii and murine dendritic cells - Slámová, M; Skallová, A; Páleníková, J; Kopecký, J (Parasite immunology, 2011)
Interaction between mouse dendritic cells (DCs) and Borrelia afzelii spirochetes was monitored on three different levels: phagocytosis of spirochetes by DCs, production of cytokines by Borrelia-stimulated DCs and the ability of Borrelia-exposed DCs to activate specific CD4+ T lymphocytes. The effect of Ixodes ricinus tick saliva on each of these interactions was examined. Tick saliva was shown to decrease the number of phagocytosing DCs. The ability of Borrelia-exposed DCs to induce both proliferation and IL-2 production by specific CD4+ T cells was significantly reduced by tick saliva. And surprisingly, we have shown an inhibitory effect of tick saliva on the production of both Th1 (TNF-α and IL-6) and Th2 (IL-10) cytokines by DCs. Our data reveal a complex inhibitory effect of tick saliva on Borrelia-DCs interaction.
Keywords: Ixodes; Borrelia burgdorferi Group; dendritické buňky; cytokiny; Female; klíště; myši inbrední C3H; Mice, Inbred C3H; zvířata; myši; Lymphocyte Activation; Saliva; Mice; fagocytóza; imunologické faktory; aktivace lymfocytů; ženské pohlaví; CD4-Positive T-Lymphocytes; Borrelia burgdorferi komplex; Dendritic Cells; Cytokines; sliny; Immunologic Factors; CD4-pozitivní T-lymfocyty; Animals; Phagocytosis